Blood group A: a risk factor for heart rupture after acute myocardial infarction - Yuan Fu; Mulei Chen; Hao Sun; Zongsheng Guo; Yuanfeng Gao; Xinchun Yang; Kuibao Li; Lefeng Wang (BMC Cardiovascular Disorders, 2020)
Abstract Introduction Studies have been performed to identify the association between ABO blood groups and coronary artery disease. However, data is scarce about the impact of ABO blood groups on heart rupture (HR) after acute myocardial infarction (AMI). Methods We conducted a retrospective case–control study that included 61 consecutive patients with HR after AMI during a period from 1 January 2012 to 1 December 2019. The controls included 600 patients who were selected randomly from 8143 AMI patients without HR in a ratio of 1:10. Univariate and multivariate logistic regression analysis were used to identify the association between ABO blood groups and HR. Results Patients with blood group A had a greater risk of HR after AMI than those with non-A blood groups (12.35% vs 7.42%, P < 0.001). After adjusting for age, gender, heart rate at admission, body mass index (BMI), and systolic blood pressure (SBP), blood group A was independently related to the increased risk of HR after AMI (OR = 2.781, 95% CI 1.174–7.198, P = 0.035), and remained as an independent risk factor of HR after AMI in different multivariate regression models. Conclusion Blood group A is significantly associated with increased HR risk after AMI.